A comparison of cognitive functioning in acute schizophrenia and depression. Issue 6 (29th May 2013) - Gooren, Tina; Schlattmann, Peter; Neu, Peter
Abstract : Objective: Even though cognitive deficits are well recognised in schizophrenia and depression, direct comparisons between the disorders are scarce in literature. This study aims to assess specificity and degree of cognitive deficits in inpatients with acute schizophrenia and unipolar major depression. Methods: A neuropsychological test battery was administered to 76 schizophrenic patients, 102 patients with unipolar major depression and 85 healthy controls (HCs), assessing verbal learning [Rey Auditory Verbal Learning Test (RAVLT)], processing speed (Trail Making Test), verbal fluency and visual memory (Wechsler Memory Scale-Revised test). Results: Both patient groups were significantly impaired compared with HCs with regard to all test outcomes. The schizophrenia group (SG) performed significantly worse in the Wechsler Memory Scale and verbal fluency than the depression group (DG). The DG reached significantly lower scores than the SG in the RAVLT delayed recall subtest. No significant group difference between SG and DG was found for the Trail Making Test and the RAVLT direct recall trails. Conclusion: Our results indicate that cognitive impairment is present in both disorders. Schizophrenic patients performed worse than patients with unipolar depression in only two of the administered tests. Differences in cognitive performance between the groups are not as general as often assumed. Therefore, during the acute phase of illness, a diagnostic classification on the grounds of the patients' neurocognitive performance has to be done with caution.